Fractionation, identification and vaccination efficacy of native antigens from the screwworm fly, Chrysomya bezziana - Riding, George; Muharsini, Sri; Pearson, Roger; ., Sukarsih; Satria, Edy; Wijffels, Gene; Willadseni, Petter (Indonesian Animal Sciences Society, 2000)
sources of potential protective antigens from the sheep blowfly Lucilia cuprina. Their importance in the screwworm fly Chrysomya bezziana has now been investigated. Purified serine proteases from Chrysomya bezziana were tested for their potential as vaccine antigens in sheep, efficacy being assessed by in vitro and in vivo assays with larval Chrysomya bezziana. No effect of vaccination was observed by the in vitro assay. However, in the in vivo challenge, larval weights were diminished in the vaccinated sheep, although larval recoveries increased marginally. Vaccination with Chrysomya bezziana peritrophic membrane does induce an effective immune response against the parasite resulting in a significant reduction in larval growth and considerable larval mortality in the in vitro assay. Sequential fractionation of the peritrophic membrane with various surfactants and chaotrophic agents of increasing solubilisation capacity resulted in the separation of discrete groups of proteins. The groups Â of fractionated proteins were tested in a vaccination trial in sheep with vaccine efficacy assessed by in vitro assays. The urea extract, guanidine-HCl extract and SDS soluble fraction each induced significant levels of protection against Chrysomya bezziana larvae but the effects were poorer than those obtained from vaccination with whole, native peritrophic membrane. Several major proteins selected from the three most protective fractions were purified by SDS polyacrylamide gel electrophoresis. Since insufficient quantities of these proteins were available for vaccination trials, they were either sequenced directly from the N-terminus or subjected to endoproteinase Lys-C digestion, followed by peptide purification and amino acid sequencing. This gave the information necessary for the expression of several of these Â roteins as recombinants in a form suitable for vaccination studies. Â Key words: Chrysomya bezziana, peritrophic membrane, vaccination, amino acid sequence, serine protease